2018
DOI: 10.1111/ejss.12546
|View full text |Cite
|
Sign up to set email alerts
|

Responses of crop productivity and physical protection of organic carbon by macroaggregates to long‐term fertilization of an Anthrosol

Abstract: Summary Soil organic carbon (SOC) sequestration in the soil of arable land has been recommended as a ‘win–win strategy’ for improving soil quality and crop productivity, and for mitigating the effects of climate change. With data from a 35‐year field experiment, we investigated the effects of organic manure and synthetic fertilizers on the mechanisms of organic carbon (OC) protection in macroaggregates and the relations between crop productivity and OC under an intensive wheat (Triticum aestivum L.) and maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…10.0 g kg −1 and 8.8 g kg −1 for the irrigated and rain-fed experiments, respectively. Our value is lower than the 20 g kg −1 reported for a rain-fed system in Alberta, Canada (Howard and Howard 1990) but is close to the average "threshold" SOC values (between 7.8 and 15.9 g kg −1 ) based on a large number of long-term experiments conducted across China (Zhang et al 2016;Xie et al 2018). The threshold value of SOC is also specific to the soil type.…”
Section: Rational Soil Carbon Contentsupporting
confidence: 53%
“…10.0 g kg −1 and 8.8 g kg −1 for the irrigated and rain-fed experiments, respectively. Our value is lower than the 20 g kg −1 reported for a rain-fed system in Alberta, Canada (Howard and Howard 1990) but is close to the average "threshold" SOC values (between 7.8 and 15.9 g kg −1 ) based on a large number of long-term experiments conducted across China (Zhang et al 2016;Xie et al 2018). The threshold value of SOC is also specific to the soil type.…”
Section: Rational Soil Carbon Contentsupporting
confidence: 53%
“…22 reported that a combination of straw and chemical fertilization increased the content of cPOM, iPOM, and S + C fractions in an Inceptisol (in Zhengzhou) but decreased in a Mollisol (in Gongzhuling). In contrast, manure application significantly increased all SOC fractions in an Ultisol 23 , Anthrosol 24 and Inceptisol 22 . Clearly, the effect of various fertilization practices on the SOC physical fractions remains largely unknown.…”
Section: Introductionmentioning
confidence: 82%
“…Many studies have demonstrated a correlation between soil quality and organic recycling (Lal, ; Oldfield et al, ). However, the crop yield response to the recycling of organic materials to fields remains unclear: Yields have reportedly increased (Akhtar et al, ; Xie et al, ), decreased (N'Dayegamiye, ), or not responded to recycling (Baldi et al, ; Hijbeek et al, ). These uncertain responses of yield have dampened local farmers' enthusiasm for recycling organic materials to their fields (Hijbeek et al, ; Oelofse et al, ).…”
Section: Introductionmentioning
confidence: 99%